Concretion of the connection “habitual residence” in the maintenance obligations Hague Protocol in the event of a wrongful removal or retention according to Regulation (EC) 2201/2003. Clarification proposed by the CJEU of May 12, 2022, case C-644/20, W. J - Durán Ayago, Antonia (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The Court of Justice of the European Union clarifies that the concept of habitual residence of the Hague Protocol on the law applicable to maintenance obligations does not have to be affected by article 10 of Regulation (EC) 2201/2003, in the framework of an illegal transfer of minors by their mother from the United Kingdom to Poland, a State in which they request and obtain alimony in accordance with Polish law, applying Article 3 of the Protocol.